L’UGTT et l’UTICA : Entre conflit ouvert et union sacrée - Héla Yousfi (L’Année du Maghreb)
The role played by the UGTT and the UTICA on the Tunisian political scene since the uprising from December 17, 2010 until today has been the subject of debates that are at least passionate. This article proposes, from their history since independence until today, to analyze the continuities and breaks in the functioning of the two most powerful organizations in Tunisia, in order to grasp the way in which the post- Ben Ali has transformed both their identity and the nature of the relationship that binds them. More specifically, it is a question of exploring how the open conflicts or the negotiated cooperation that took place at different times between 2011 and 2015 have reconfigured the place of these two organizations in a rapidly changing political and social field. We will also discuss the impact of these political developments on the relationship between the two organizations and the new economic and social challenges they face.